Best Social Entrepreneurship Teaching and Learning Strategies for Promoting Students' Social Entrepreneurial Minds: A Scoping Review - Hariyaty Ab Wahid, Rafiduraida Abdul Rahman, Wan Salmuni Wan Mustaffa, Noor Lela Ahmad, Mohamad Rohieszan Ramdan (Tanjung Malim, 2024)
Best Social Entrepreneurship Teaching and Learning Strategies for Promoting Students' Social Entrepreneurial Minds: A Scoping Review by Hariyaty Ab Wahid, Rafiduraida Abdul Rahman, Wan Salmuni Wan Mustaffa, Noor Lela Ahmad, Mohamad Rohieszan Ramdan